HUBUNGAN ANTARA PEMAHAMAN SEJARAH PERGERAKAN NASIONAL INDONESIA DAN WAWASAN KEBANGSAAN TERHADAP SIKAP PATRIOTISME SISWA - Prabowo, Tomi Budi; S, Leo Agung; Herimanto, Herimanto (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The objectives of research were to find out: 1) the relationship between understanding of national movement history with attitude of patriotism of the students. 2) The relationship between the national insights with attitude of patriotism of the students. 3) The relationship between understanding of national movement history and the national insights with attitude of patriotism of the student. This research using quantitative method with correlational research design. The population of research was all of the XI grades of SMA Batik 2 Surakarta of academic year 2017/2018, consisting of 248 students. The sample used is of 71 students. The sample was taken using random sampling technique. The technique of collecting data used were questionnaire. The technique of collecting data used were questionnaire. The technique of analyzing data used was a multiple linear regression analysis, t-test, multiple correlation analysis (F-test), R2, and relative and effective contribution. The conclusion of research were as: 1) there is a negatively relationship between the relationship between understanding of national movement history with attitude of patriotism of the students. It could be seen from the multiple linear analysis (t-test) showing that tstatistic < ttable, 0,951 < 1,687 and the significance value > 0,05 of 0,329. The Errors that occurred allegedly came from preparation of test. Comprehension test about allegedly used the elusive answer choices. Limitations time in test-taking.2) There was a positive relationship between the national insights with attitude of patriotism of the students. It could be seen from the multiple linear analysis (t-test) showing that tstatistic > ttable, 7,794 > 1,676 and the significance value < 0,05, of 0,000. 3) There was a positive relationship between understanding of national movement history and the national insights with attitude of patriotism of the students. It could be seen from the multiple linear regression variance analysis (F-test) showing that Fstatistic > Ftable, 52,662 > 2,38 and the significance value < < 0,05 of 0,000.